The Form and Content of Ọbasa’s Weekly Newspaper: The Yorùbá News - Clement Adeniyi Akangbe (Yoruba Studies Review)
The Yorubà News, published by Obasa ̣ , co-pioneered journalism, nay publishing, in Yorùbá language in southwestern Nigeria. Based in Ìbàdan and ̀ published by Ìlarè Printers, ̣́ The Yorùbá News, a bi-lingual serial in English and Yorùbá languages, remarkably had varying contents and wide circulation covering its locale, Íbàdan significantly; the southern protectorate, particularly Yorùbá land appreciably; and the entire nation, Nigeria marginally. Published weekly, Obasa – the Editor and Proprietor – successfully edited ̣ The Yorubà News ́ for over two decades from 1924 – 1945 when he died. Adopting the Diffusion of Innovations theory, this study examines the form and content of the newspaper. The form examines the structure and layout of the newspaper while the content discusses and evaluates issues covered in the publication. The form of The Yorùbá News is discussed in the context of the print media as a periodical by taking technical cognizance of its physical features: format, design and layout, typography, columns, paper, size and production quality. Content-wise, the paper exhaustively describes the subject matters of The Yorubà News ́ by dwelling critically on the issues raised, examining in details and critiquing its recurrent subject matters notably: the news stories, editorials, cover, advertorials, news and notes, etc. The inter-dependence of form and content is also examined to bring to the fore the social, cultural, political, and economic values of the maiden Yorùbá Newspaper: The Yorùbá News.